2021
DOI: 10.1155/2021/9516427
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Seawater Pearl Powder on UV-Induced Photoaging in Mouse Skin

Abstract: The objective of this study was to investigate the therapeutic effect of seawater pearl powder (SPP) on ultraviolet (UV) irradiation-induced photoaging in mouse skin. The protein and trace elements in SPP were detected by liquid chromatography-mass spectrometry, atomic fluorescence spectrometry, and inductively coupled plasma-atomic emission spectrometry. The effect of SPP on treating skin damage resulting from UV-induced photoaging was observed by gross physical appearance and histopathological analysis. Oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As mentioned before, several studies on pearl powder and extracts have demonstrated their whitening effect [ 17 , 18 , 19 , 20 ]. This is the first time the purified pearl extract HCP on MNT-1 human melanoma cells has been studied to observe the whitening effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, several studies on pearl powder and extracts have demonstrated their whitening effect [ 17 , 18 , 19 , 20 ]. This is the first time the purified pearl extract HCP on MNT-1 human melanoma cells has been studied to observe the whitening effect.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, preventing skin hyperpigmentation and eliminating melanin formation is a time-consuming process that can cause psychological distress to consumers, and the use of whitening agents can help with this process. However, some of skin-whitening agents such as rhododendrol and hydroquinone cause significant side-effects such as leukoderma and erythema [ 16 , 17 ]. The development of safe and effective whitening agents is in line with market demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearl extract can reduce the inflammation and apoptosis of human skin keratinocytes under UVB irradiation [14], and the aqueous extract of pearl can reduce the number of human skin fibroblasts that age under UVB irradiation [15]. Moreover, our group has carried out preliminary research and found that powdered seawater pearls can prevent and treat mouse skin photoaging, and its mechanism chiefly involves the removal of excessive ROS from photoaging skin [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage, the research group selected seawater pearls for hydrolysis and obtained a series of products such as seawater pearl hydrolysate (SPH), hydrolyzed seawater pearl powder, and Zhenmi tablets and successfully developed the hydrolyzed pearl technology (national invention patents zl95106283.2, zl95108034.2, and zl95107894.1). It has been found that seawater pearl powder can prevent and treat skin photoaging in mice, and its mechanism involves the removal of excessive reactive oxygen species (ROS) from photoaging skin [6,7]. erefore, we studied the effect of seawater pearls on skin photoaging at the cellular level using a UVA-induced photoaging model of HSF cells to detect the ROS, oxidative damage, antioxidant level, collagen, and level of aging before and after SPH intervention on HSF cells.…”
Section: Introductionmentioning
confidence: 99%